Pelatihan dan Pendampingan Media Pembelajaran Daring di SD Saraswati 4 Denpasar - Gusti Ayu Dewi Setiawati; Anak Agung Putu Arsana; Ni Wayan Ekayanti (Sevanam: Jurnal Pengabdian Masyarakat, 2022)
The implementation of the Community Service Program (PkM) at SD Saraswati 4 Denpasar in Renon Village which involved 20 teachers from class I to class VI at SD Saraswati 4 Denpasar aims to improve the quality of education in terms of optimizing online learning during the Covid 19 pandemic. All of these activities has implemented through training and simulations, methods in the form of training and assistance on the use of media in the distance learning process / in the network (online). After carrying out the training, an online media application simulation assistance was carried out in learning practice. The results of this activity indicate that partner teachers have been able to use online media in distance learning. These teachers have been able to apply online learning media such as Whatsapp (WA), Google Classroom, Google Meet, and Zoom. The teacher showed an enthusiastic attitude in receiving the material in this program. This can be observed through several indicators such as; the level of attendance during the activity, enthusiasm in participating in learning, attitude in practicing, asking questions related to the material that has been submitted and responding to questions asked properly. The results of the learning evaluation show that partner teachers who previously could not use online media in learning have been able to apply online learning media such as Whatsapp (WA), Google Classroom, Google Meet, and Zoom. Key words: Training , Assistance, Online Media, SD Saraswati 4 Denpasar